The Population dynamics of fruit flies and correlation matrix with weather and host variables in mango (Mangifera indica) orchards - R, MEGHA; SINGH, SANJAY K; SRIVASTAV, MANISH; KALIA, VINAY; SHARMA, NIMISHA; KUMAR, CHAVLESH; SINGH, NARENDRA (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out in the Mango orchards at Indian Agricultural Research Institute, New Delhi during 2020–2021 and 2021–2022 and aimed at analysing the population dynamics of fruit fly (Bactrocera dorsalis) species after putting the requisite number of methyl eugenol traps (@6 per acre). Weekly monitoring of fruit fly populations was performed and correlated with various weather parameters. Among the fruit fly species, the oriental fruit fly was found to be the most prevalent and abundant, followed by B. zonata, B. correcta, and B. cucurbitae. Fruit fly populations peaked in mango plantations between June and July, coinciding with the ripening time and the occurrence of humid conditions and rainfall. Multiple factors, including weather conditions, the presence of preferred host plants, and alternative hosts, fruits characteristics were found to influence the dynamics of fruit fly populations. The seasonal trap captures of male fruit flies showed a moderately significant negative correlation (-0.612*) with maximum but significant positive correlation with the minimum temperature (0.701**). However, a positive correlation was observed between relative humidity (r = 0.924**) and rainfall (r = 0.721**) with the fluctuations of fruit fly populations across all the monitored orchard sites.